2019
DOI: 10.1016/j.celrep.2019.09.088
|View full text |Cite
|
Sign up to set email alerts
|

A Systems-Based Map of Human Brain Cell-Type Enriched Genes and Malignancy-Associated Endothelial Changes

Abstract: Highlights d Cell-type reference mRNA used to profile cell-specific transcripts from bulk RNA-seq d RNA-seq of 238 unfractionated human brain samples from two cohorts was analyzed d Endothelium-enriched transcriptome was profiled, together with four other cell types d RNA-seq of 401 unfractionated glioblastomas analyzed for tumor endothelial markers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 96 publications
0
27
0
Order By: Relevance
“…Previous bulk analysis–based transcriptomic studies have revealed limited insights into the characteristics of ECs in normal brain and GBM ( 7 , 8 ). In bulk RNA analysis, cellular heterogeneity gets lost in the average of gene expression from all cells, and contaminations from other cell types cannot be deduced, together posing severe limitations to interpretations and the possibilities for correctly assigning EC-specific changes and their heterogeneity within the EC population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous bulk analysis–based transcriptomic studies have revealed limited insights into the characteristics of ECs in normal brain and GBM ( 7 , 8 ). In bulk RNA analysis, cellular heterogeneity gets lost in the average of gene expression from all cells, and contaminations from other cell types cannot be deduced, together posing severe limitations to interpretations and the possibilities for correctly assigning EC-specific changes and their heterogeneity within the EC population.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular alteration of ECs has been observed in patients and animal models of many brain diseases, including stroke, multiple sclerosis, traumatic brain injury and GBM (5,6). By analysis of bulk mRNA isolated from brain ECs, we and others have shown that the abnormal vessels in GBM are associated with a distinct gene signature (7)(8)(9). However, the more precise characteristics of endothelial gene expression in GBM, including possible heterogeneity that cannot be resolved using bulk methods, is still poorly understood.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, an up-regulation of 3884 out of 13,485 genes is seen from P0D0 to P0D7 (≥1.5-fold, p ≤ 0.05), most probably representing endothelial-specific genes, and thus reflecting the in vitro selection of the endothelial cell population. The degree of purity of P0D0 and in vitro-selected P0D7 and P1D7 samples was assessed through probing the transcriptome data for the expression of 5 acknowledged cell type specific genes [18][19][20][21] for astrocytes (BMPR1B, GFAP, ALDH1L1, SOX9, AQP4), neurons (TMEM130, RELN, STMN2, SYT1, SYN1), oligodendrocytes (MAG, PLP1, MOG, MOBP, MBP), and microglia (AIF1, C1QA, C1QB, CX3CR1, TNF), and 10 genes for endothelial cells (SLC2A1/GLUT1, EPAS1, ITM2A, CLDN5, BSG, CD34, VWF, PECAM1, CDH5, ESAM) (Figure 1(B2)). All non-endothelial cell markers see their expression being switched-off in P0D7 and P1D7 cell populations, while the expression of the selected endothelial genes is either maintained or even increased in both the P0D7 and P1D7 cell populations, in comparison to P0D0 (Figure 1(C1)).…”
Section: Transcriptional Profiling Of Brain Microvasculaturementioning
confidence: 99%
“…To explore the effect of vascular ECs on contrast enhancement in MRI, we first identified EC-enriched genes by a systematic approach through performing the correlation analysis of the expression profiles of all gene transcripts to the known EC marker gene as previously described (20,21). A high average correlation coefficient with those EC marker genes indicates the enrichment of the genes in EC (20,21).…”
Section: Identification Of Endothelial-enriched Genes In Gbmmentioning
confidence: 99%
“…To explore the effect of vascular ECs on contrast enhancement in MRI, we first identified EC-enriched genes by a systematic approach through performing the correlation analysis of the expression profiles of all gene transcripts to the known EC marker gene as previously described (20,21). A high average correlation coefficient with those EC marker genes indicates the enrichment of the genes in EC (20,21). We analyzed transcriptome data from 128 GBM cases with available MRI records in TCGA (Table S1) to produce the average correlation values between EC marker genes (CDH5, CLDN5, VWF) and the other >20,000 protein encoding genes, yielding 343 EC-enriched genes manifesting correlation coefficient >0.3 (Figures 1A, B and Table S2).…”
Section: Identification Of Endothelial-enriched Genes In Gbmmentioning
confidence: 99%